A comparative melissopalynological study of royal jelly from Turkey. Issue 4 (4th July 2022) - Yil, Gulsah; Karlidag, Semiramis; Akyol, Abuzer; Koseman, Abdurrahman; Uyumlu, Ayşe Burçin; Yilmaztekin, Murat; Erdogan, Selim; Seker, Ibrahim
Abstract: Three treatments (Glucose, Sucrose, Bee Feed Syrup) were used to examine the influence of supplementary feeding on the pollen spectrum of the royal jelly produced by Apis mellifera L. colonies. Apis mellifera colonies were located in the Battalgazi and Dogansehir districts of Malatya province in Turkey. In total 255 royal jelly samples were investigated and the analysis recorded over 30 taxa. In both sites the control group heavily utilised Quercus, Verbascum, Astragalus, and Lamiaceae. The feeding treatments saw Quercus, Verbascum, and Astragalus still being used but in different proportions. The utilisation of Lamiaceae was much reduced and Echium became an important component in colonies that had supplementary feeding.